Computing Technologies in the Kitchen: The Living Cookbook as a Design for Mindful Cooking Experiences - Terrenghi, Lucia (Material Culture Review, 2009)
This article considers how multimedia and embedded computing technologies can support the domestic learning of cooking, thus considering the family as a community of practice and the cooking process as a sharable activity. Such a vision is exemplified with the Living Cookbook computer appliance: This relies on the video capture and retrieval of family members’ cooking sessions, so as to enable the creation and sharing of personalized, multimedia cooking instructions. Résumé Cet article examine la manière dont les outils informatiques multimédias peuvent venir à l’appui de l’apprentissage de la cuisine à la maison, en considérant la famille comme une communauté de pratiques, et le processus de la cuisine comme une activité que l’on peut partager. Nous présenterons l’exemple d’une telle conception par l’intermédiaire de « l’ustensile de cuisine » Living Cookbook [livre de cuisine vivant]. Celui-ci sert à accéder à des vidéos de sessions de cuisine familiale, afin de permettre la création et le partage d’instructions de cuisine personnalisées et multimédias.